2013
DOI: 10.1371/journal.pone.0056503
|View full text |Cite
|
Sign up to set email alerts
|

Tremulatory and Abdomen Vibration Signals Enable Communication through Air in the Stink Bug Euschistus heros

Abstract: Communication by substrate-borne mechanical signals is widespread among animals but remains one of their least understood communication channels. Past studies of vibrational communication in insects have been oriented predominantly to communication during mating, showing that species- and sex-specific vibrational signals enable recognition and localization of potential mates on continuous solid substrates. No special attention has been paid to vibrational signals with less obvious specificity as well as to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…The vibrational signals of H. halys in this stage notably include tremulation, which is a separate mechanism involving the production of short, broadband pulses by shaking the whole body. Such signals are described during courtship for other Pentatomid species, such as Podisus maculiventris (Žunič et al ., ) and Euschistus heros (Kavčič et al ., ). Furthermore, numerous transitions between song types are observed, perhaps hinting at the evolution of signal repertoires from a ‘basic’ type.…”
Section: Discussionmentioning
confidence: 97%
“…The vibrational signals of H. halys in this stage notably include tremulation, which is a separate mechanism involving the production of short, broadband pulses by shaking the whole body. Such signals are described during courtship for other Pentatomid species, such as Podisus maculiventris (Žunič et al ., ) and Euschistus heros (Kavčič et al ., ). Furthermore, numerous transitions between song types are observed, perhaps hinting at the evolution of signal repertoires from a ‘basic’ type.…”
Section: Discussionmentioning
confidence: 97%
“…Hill and Wessel (2016) define tremulation as a shaking or trembling behavior that induces vibrations in the substrate, often through the legs, with no percussive impact. This communication via surface-borne vibrations is widely documented in arthropods, such as orthopterans (Cocroft, Shugart, Konrad, & Tibbs, 2006) and hemipterans (Kavčič, Čokl, Laumann, Blassioli-Moraes & Borges, 2013), but also had been reported in some vertebrates, such as tree frogs (Caldwell et al, 2010), salamanders (Christensen, Lauridsen, Christensen-Dalsgaard, Pedersen, & Madsen, 2015) and seals (Bishop, Denton, Pomeroy, & Twiss, 2015). The analysis of this vibrational signaling in animals, known as biotremology, allows a better understanding of communication through these signals, the propagation process in the environment and how physical variables affect this behavior (Mortimer, 2017).…”
mentioning
confidence: 80%
“…Nevertheless, Eriksson et al [44] described signalling between a male and female leafhopper Scaphoideus titanus (Ball) by vibratory signals transmitted over the air at a six cm distance between mechanically isolated leaves. Kavčič et al [45] confirmed airborne communication up to six cm distance in the stink bug species E. heros. During transmission through the air between mechanically isolated leaves, signal spectra become narrower by increased attenuation of frequencies above 300 Hz, and the signal's amplitude decreases by 20 to 30 dB at three cm and by 25 to 35 dB at six cm distance.…”
Section: -Communication Through Air and Substratementioning
confidence: 94%
“…Tremulatory signals are produced by vigorous shaking of the whole body parallel to the substrate, with legs firmly standing on it [51,81,82]. Tremulatory signals produced in Pentatominae [45] and Asopinae [81] share common amplitude, temporal and frequency characteristics. The characteristic plant-recorded tremulatory signals of amplitudes up to 5 mm/s, duration below 0.5 s and irregular repetition rate are composed of a short, high frequency onset followed by the longer low frequency tail with the decaying amplitude resembling plant resonance.…”
Section: -Production and Characteristics Of Communication Signalsmentioning
confidence: 99%
See 1 more Smart Citation